PENGARUH MODEL THINK PAIR SHARE TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA KELAS V SDN 1 SUKARARA TAHUN AJARAN 2024/2025 - Munaenah Apriliani; Darmiany; Iva Nurmawanti; Vivi Rachmatul Hidayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The mathematical representation skills of fifth grade students at SDN 1 Sukarara are still relatively low which is caused by several factors such as the lack of learning facilities, the use of media and leaning methods that are less diverse. This study aims to determine the effect of the Think Pair Share model on the mathematical representation skills of fifth grade students at SDN 1 Sukarara in the 2024/2025 academic year. The type of research used in this study is a quasi-experiment with a nonequivalent control group design. The data collection techniques used were observation and essay tests. The data analysis method used is the non-parametric test with the Mann Whitney U test. The Asymp. Sig (2-tailed) value is 0.000 < 0.05, then Ha can be accepted and H0 is rejected, which means there is a difference in mathematical representation ability between the experimental class and the control class. In addition, the N-Gain test was also carried out with the acquisition of an average value in the experimental class of 0.787262 or 79%, which means that the Think Pair Share learning model on the mathematical representation skills of fifth grade students at SDN 1 Sukarara is effective and categorized as high.